Comment on "The Influence of Risk Assessment Instrument Scores on Evaluators' Risk Opinions and Sexual Offender Containment Recommendations". (September 2017) - Lobanov-Rostovsky, Christopher
The work of the Colorado Sex Offender Management Board (SOMB) has been called into question as a result of the manuscript "The Influence of Risk Assessment Instrument Scores on the Evaluators' Risk Opinions and Sexual Offender Containment Recommendations" published in Criminal Justice and Behavior (2017). This response covers the following areas: significant nomenclature problems used to describe the Adult Standards and Guidelines, the dated nature of the SOMB citations in the manuscript, the flaws in the interpretation of the use of the 17 SOMB risk factors and the SOMB policy related to risk assessment, a potential confounding variable that may explain the results obtained, and finally the work of the SOMB to foster the use of validated risk assessment instruments and evidence-based policies and practices. The SOMB takes pride in providing up-to-date, research-supported practices for its providers and would never intentionally do otherwise, as suggested by the article.